Blasting Claims 101: An Introduction to the Defense of Claims - Joshua A. Bennett (International Society of Explosives Engineers, 2016)
"Lawsuits where owners allege their property has been damaged by nearby blasting routinely costblasting companies, explosives engineers, and others in the field both time and money. When ownersfeel the vibration of a blast, they immediately begin to look for damage and usually find cracking thatwas, in fact, present prior to the blasting occurring. When those owners begin to talk to their neighbors and legal counsel, blasting entities suddenly have multiple lawsuits being filed as a result of the same blast."